Anticoagulant activity in salivary gland homogenates of Thyrsopelma guianense (Diptera: Simuliidae), the primary vector of onchocerciasis in the Brazilian Amazon - Andrezza Campos Chagas; Jansen Fernandes Medeiros; Spartaco Astolfi-Filho; Victor Py-Daniel (Memorias do Instituto Oswaldo Cruz, 2010)
In this study, anticoagulant activity was detected in salivary gland homogenates (SGHs) of Thyrsopelma guianense (Diptera: Simuliidae). The SGH yielded 1.07 μg ± 0.03 (n = 15) of total soluble protein per pair of glands. In addition, following SDS-PAGE (12.5% gel) and silver nitrate staining, 12 polypeptides with molecular weights ranging from 14-69 kDa were detected in all physiological ages analyzed (12 h, 24 h, 48 h and 72 h following emergence). Coagulation bioassays showed that the SGHs had activities that interacted at all levels of coagulation (the intrinsic, extrinsic and common pathways), by extending the plasma recalcification time, prothrombin time, thrombin time. This is the first report on the activity of salivary gland proteins from the main vector of onchocerciasis in Brazil. We also suggest detailed studies on the morphology and function of the salivary glands in order to understand the role of these proteins in host/vector interactions.